THE EFFECT OF KNOW, WANT, LEARNED (KWL) PLUS STRATEGY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MTS ASSYAKIRIN BANGKO PUSAKO IN COMPREHENDING FOLKLORE - Lilis Swardani; Jismulatif Jismulatif; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to investigate the effect of Know, Want, Learned (KWL) Plus strategy on the ability of the second year students of MTs Assyakirin Bangko Pusako in comprehending folklore. In conducting the research, pre-experimental research with one group pre-test post-test design was used. The sample of this research was the students of class VIII E which consisted of 25 students. The pre-test was administered before the treatment. After the treatment was applied for four meetings using KWL Plus strategy, a post-test was administered. The data were analyzed using t-test formula. From the calculation, the writer found that the value of t-test was 9.005 while t-table was 2.063. Since the t-test value was larger than that of t-table, the alternative hypothesis of this research was accepted and null hypothesis was rejected. It means that there was a significant effect of Know, Want, Learned (KWL) Plus strategy on the ability of the second year students of MTs Assyakirin Bangko Pusako in comprehending folklore.Key Words: Know, Want, Learned (KWL) Plus strategy, reading comprehension, folklore